Reduction in the Number of Varicella-Zoster Virus-Specific T-Cells in Immunocompromised Children with Varicella - Onoyama, Sagano; Nakayama, Hideki; Tanaka, Tamami; Ishimura, Masataka; Hoshina, Takayuki; Kanno, Shunsuke; Murata, Kenji; Koga, Yuhki; Ohga, Shouichi (The Tohoku Journal of Experimental Medicine, 2020)
Varicella zoster virus (VZV) causes a life-threatening infection in immunocompromised hosts. The immune response to VZV of healthy subjects has been rigorously assessed, but little is known about that of immunocompromised individuals. This study aimed to clarify the primary response to VZV infection in immunocompromised children. This prospective study enrolled six immunocompromised children (median age, 33 months; range, 20-62) receiving steroids or immunosuppressants, and 10 immunocompetent children (median age, 32 months; range, 15-81) with varicella. The immunocompromised children were three patients with acute lymphoblastic leukemia, two recipients with liver transplantation and one patient with juvenile idiopathic arthritis. Interferon-γ-producing CD69+T-cells produced by VZV stimulation (VZV-specific T-cells) were studied during the acute or convalescent phase. To further address the direct effect of immunosuppressants, we analyzed the number of VZV-specific T-cells after stimulating peripheral blood mononuclear cells obtained from healthy adults with live-attenuated VZV with or without prednisolone, cyclosporine-A, or tacrolimus. The circulating numbers of lymphocytes in the convalescent stage but not acute stage were lower in immunocompromised children compared with immunocompetent children. In the acute stage, immunocompromised patients showed lower VZV-specific CD8+T-cell counts than immunocompetent subjects. In contrast, in the convalescent phase, immunocompromised patients had lower VZV-specific CD4+T-cell counts than immunocompetent hosts. The in vitro culture of activated lymphocytes with prednisolone or immunosuppressants significantly decreased the proportion of VZV-specific CD4+T-cells. In conclusion, the decreased numbers of VZV-specific CD8+T-cells during the acute phase and VZV-specific CD4+T-cells during the convalescent phase of disease may account for severe varicella in immunocompromised children.